Improvising service broker policies in fog integrated cloud environment. (1st July 2022) - Bisht, Jyoti; Subrahmanyam, V.V.
With the huge amount of internet users and accelerating IoT devices load on the network is increasing day-by-day, cloud computing technology is offering services to its customer on a demand basis with some overheads in response time. Fog integrated cloud computing is one of the solutions which can reduce the response time due to its proximity to users. However, this technology also has certain challenges like task-scheduling and load-balancing among servers due to limited resources. In this paper we are proposing two dynamic service broker policies, modified-service proximity and modified-optimise response time. These are devised after going through the gaps of existing policies – service proximity (SP) and optimise response time (ORT). Further, through simulations it is proved that modified-SP gives better response time and processing time than SP and modified-ORT gives better response time than ORT at the cost of increased processing time.